S60 smartphone quality assurance : a guide for mobile engineers and developers - Laitinen, Saila (John Wiley, 2007)
S60 is the world leading smartphone platform. It has gained this position due to the huge developer base innovating on top of the S60 platform, the Product Creation Community who can provide expertise in different device program phases and tasks and the user-friendly interface that the platform provides.